Manipulation of the Complement System for Benefit in Sepsis - Peter A. Ward; Ren-Feng Guo; Niels C. Riedemann (Critical Care Research and Practice)
There is evidence in sepsis, both in rodents and in humans, that activation of the complement system results in excessive production of C5a, which triggers a series of events leading to septic shock, multiorgan failure, and lethality. In rodents following cecal ligation and puncture (CLP), which induces polymicrobial sepsis, in vivo blockade of C5a using neutralizing antibodies dramatically improved survival, reduced apoptosis of lymphoid cells, and attenuated the ensuing coagulopathy. Based on these data, it seems reasonable to consider therapeutic blockade of C5a in humans entering into sepsis and septic shock. Strategies for the development of such an antibody for use in humans are presented.